PJTV as a Sunda Cultural Socialization Media - Nurhayat E, Itsna; Tanziil S, Muhammad (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research aims to find out how PJTV as one of the local televisions in Bandung socializes Sundanesse culture through television media, and also to determine the factors that support and hinder PJTV in socializing Sundanese culture as an effort to preserve it. The research method used is descriptive qualitative method. Sampling was done by purposive sampling, namely selecting certain people who are considered important and representative. This research uses a structural functional approach by Talcott Parsons which states that in explaining functional structural existence it can be observed from the existence of individuals who are integrated in a system, and this condition occurs from functional and structural relationships and is supported by the existence of socializatiuon and social control mechanisms that run constantly.